Benign multicystic peritoneal mesothelioma: case reports and review of the literature - Giuliani, Jacopo; Marzola, Marina; Urbini, Benedetta; Indelli, Monica; Pizzutilo, Pamela; Sala, Simone; Pedriali, Massimo; Martinello, Ruby; Feo, Carlo; Lelli, Giorgio (European Journal of Oncology and Environmental Health, 2010)
Benign multicystic peritoneal mesothelioma is a very rare benign cystic tumor; at present approximately 130 cases have been reported. It more frequently occurs in females (87%), expecially in the pelvic area of the cul-de-sac, uterus and rectum; the pathogenesis has remained controversial. Abdominal pain is the most common symptom (75%). Ultrasound, Computerized Tomography (CT) and magnetic resonance imaging are helpful, but the diagnosis is confirmed by histopathological and immunohistochemical examination. Benign multicystic peritoneal mesothelioma shows high recurrence after surgical resection, but it does not present a tendency to transform into malignancy. Surgery is the only effective treatment, and peritonectomy is recommended. A prolonged systematic followup of these patients, perhaps for all life, is required. Here we report two cases that underwent surgery for benign multicystic peritoneal mesothelioma. In the first case the lesion was a multicystic fluid mass of the large intestine, while in the second one a smaller peritoneal mass was reported. In both cases the pathological result was a benign multicystic peritoneal mesothelioma. After surgery, we decided to continue with a prolonged systematic follow-up.